The question of God : C.S. Lewis and Sigmund Freud debate God, love, sex, and the meaning of life - Nicholi, Armand M., 1928- (New York : Free Press, 2002)
"Many of history's greatest thinkers have wrestled with the ultimate question of belief and nonbelief in God. Though it might seem unlikely that any new arguments could possibly be raised on either side, the twentieth century managed to produce two men who each made brilliant, new, and lasting arguments, one in favor of belief and one opposed. Few spokesmen have ever championed their respective positions better than Sigmund Freud and C.S. Lewis. Sadly, as far as we know, they never met or debated each other directly." "In The Question of God their arguments are placed side by side, as if they were standing at podiums in a shared room. Both thought carefully about the flaws and alternatives to their positions; each considered the other's views. Both men considered the problem of pain and suffering, the nature of love and sex, and the ultimate meaning of life and death. Here, with their debate made explicit, we can take ringside seats at one of history's most profound encounters."--Jacket
The protagonists : the lives of Sigmund Freud and C.S. Lewis -- The Creator : is there an intelligence beyond the universe? -- Conscience : is there a universal moral law? -- The great transition : which road to reality? -- Happiness : what is the source of our greatest enjoyment in life? -- Sex : is the pursuit of pleasure our only purpose? -- Love : is all love sublimated sex? -- Pain : how can we resolve the problem of suffering? -- Death : is death our only destiny?
Includes bibliographical references (p. 282-285) and index
Keywords: Lewis, C. S. -- 1898-1963; Freud, Sigmund, -- 1856-1939; God -- Proof